Clinical decision-making in patients with non-ST-segment-elevation myocardial infarction: more than risk stratification - Xiang, Guangze; Cao, Gaoyang; Gao, Menghan; Hu, Tianli; He, Wujian; Gu, Chunxia; Hong, Xulin (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study aimed to explore the association between risk stratification and total occlusion (TO) of the culprit artery and multivessel disease (MVD) in patients with non-ST-segment elevation myocardial infarction (NSTEMI) and to obtain more data on clinical decision-making in addition to risk stratification.We retrospectively collected data from 835 NSTEMI patients admitted to our hospital between January 1, 2016, and August 1, 2022. All patients underwent percutaneous coronary intervention (PCI) within 72 h of admission. We excluded patients with a history of cardiac arrest, myocardial infarction, coronary artery bypass grafting, or PCI. Univariate and multivariate regression analyses were performed to determine predictors of acute TO andResults: A total of 349 (41.8%) patients presented with a TO culprit vessel, whereas 486 (58.2%) had a patent culprit vessel. Thrombolysis in myocardial infarction (TIMI) and GRACE risk stratifications were similar between the two groups (P=0.712 and P=0.991, respectively). The TO infarct vessel was more commonly observed in the left circumflex artery (LCX). Patients with TO were more likely to develop MVD (P=0.004). Univariate and multivariate linear regression analyses were performed to evaluate the role of variables in the presence of TO and MVD in NSTEMI patients. Finally, regional wall motion abnormalities (RWMAs) (odds ratio (OR) =4.022; confidence interval (CI) (2.782-5.813); P<0.001) were significantly linked to TO after adjusting for potentially related variables. Furthermore, age (OR=1.032; CI (1.018-1.047); P <0.001), hypertension (OR=1.499; CI (1.048-2.144); P=0.027), and diabetes mellitus (OR=3.007; CI (1.764-5.125); P<0.001) were independent predictors of MVD in NSTEMI patients. TIMI and GRACE risk scores were related to MVD prevalence in the multivariate logistic regression model. Patients with a TO culprit vessel exhibited a higher risk of out-of-hospital cardiac death following a two-year follow-up than those without a TO culprit vessel (P=0.022).TIMI and GRACE risk scores were not associated with the TO of the culprit artery; however, they correlated with the prevalence of MVD in NSTEMI patients. RWMAS is an independent predictor of acute TO in NSTEMI patients. Patients with a TO culprit vessel had worse clinical outcomes than those without a TO culprit vessel.